Luteinizing hormone induces expression of 11beta-hydroxysteroid dehydrogenase type 2 in rat Leydig cells - Zhang Ping; Wang Qian; Gao Hui-Bao (BMC, 2009)
Abstract Background Leydig cells are the primary source of testosterone in male vertebrates. The biosynthesis of testosterone in Leydig cells is strictly dependent on luteinizing hormone (LH). On the other hand, it can be directly inhibited by excessive glucocorticoid (Corticosterone, CORT, in rats) which is beyond the protective capability of 11beta-Hydroxysteroid dehydrogenase type 1 (11beta-HSD1) and type 2 (11beta-HSD2; encoded by gene Hsd11b2 in rats) in Leydig cells. Our previous study found that LH increases 11beta-HSD1 expression in rat Leydig cells, but the effect of LH on the expression and activity of 11beta-HSD2 is not investigated yet. Methods The Leydig cells were isolated from male Sprague-Dawley rats (90 days of age). After Leydig cells were incubated either for 24 h with various concentrations of LH (2.5, 5, 10 and 20 ng/mL) or for different time periods (2, 8, 12 and 24 h) with 20 ng/mL LH, the mRNA expression of 11beta-HSD2 was measured by real-time PCR. 11beta-HSD2 protein levels in Leydig cells were assayed by Western Blot and 11beta-HSD2 enzyme activity was determined by calculating the ratio of conversion of [3H]CORT to [3H]11-dehydrocorticosterone by 24 h after stimulation with 20 ng/ml LH. Four reporter gene plasmids containing various lengths of Hsd11b2 promoter region were constructed and transfected into mouse Leydig tumor cells to investigate the effect of LH on Hsd11b2 transcription. A glucocorticoid-responsive reporter gene plasmid, GRE-Luc, was constructed. To evaluate influence of LH on intracellular glucocorticoid level, rat Leydig cells were transfected with GRE-Luc, and luciferase activities were measured after incubation with CORT alone or CORT plus LH. Results We observed dose- and temporal-dependent induction of rat 11beta-HSD2 mRNA expression in Leydig cells subject to LH stimulation. The protein and enzyme activity of 11beta-HSD2 and the luciferase activity of reporter gene driven by promoter regions of Hsd11b2 were increased by LH treatment. LH decreased the glucocorticoid-induced luciferase activity of GRE-Luc reporter gene. Conclusion The results of the present study suggest that LH increases the expression and enzyme activity of 11beta-HSD2, and therefore enhances capacity for oxidative inactivation of glucocorticoid in rat Leydig cells in vitro.